A concept for planning and management of on-site and centralised municipal wastewater treatment systems, a case study in Bangkok, Thailand. II: Scenario-based pollutant load analysis - Yoshiaki Tsuzuki (2018)
Scenario-based pollutant load analysis was conducted to develop a part of a concept for planning and management of wastewater treatment systems (WWTSs) under the mixture conditions of centralised and on-site WWTSs. Pollutant discharge indicators and pollutant removal efficiency functions were applied from another paper in the series, which were developed based on the existing conditions in urban and peri-urban areas of Bangkok, Thailand. Two scenarios were developed to describe development directions of the mixture conditions. Scenario 1 involves keeping the on-site wastewater treatment plants (WWTPs) within the areas of centralised WWTSs. Scenario 2 is dividing the centralised and on-site WWTS areas. Comparison of the smallest values of total pollutant discharge per capita (PDC total ) between Scenarios 1 and 2 showed that the smallest PDC total in Scenario 1 was smaller than that in Scenario 2 for biological oxygen demand, chemical oxygen demand and total phosphorus whereas the smallest PDC total in Scenario 2 was smaller than that in Scenario 1 for total nitrogen, total coliforms and faecal coliforms. The results suggest that the mixture conditions could be a possible reason for smaller pollutant concentrations at centralised WWTPs. Quantitative scenario-based estimation of PDC total is useful and a prerequisite in planning and management of WWTSs. © IWA Publishing 2013.